An open-label, single-arm study evaluating the immunogenicity and safety of the hepatitis B vaccine HepB-CpG (HEPLISAV-B®) in adults receiving hemodialysis. Issue 25 (8th June 2021) - Awad, Ahmed M.; Ntoso, Adu; Connaire, Jeffrey J.; Hernandez, German T.; Dhillon, Kiranjit; Rich, Lisa; Henderson, Heather; Lynn, Robert; Hyer, Randall N.; Xie, Fang; Erby, Kimberly; Janssen, Robert S.; et al.
Highlights: Phase 1 study of HEPLISAV-B in hemodialysis patients. Four doses of HEPLISAV-B induced high level of seroprotection and were well tolerated. Abstract: Background: Hemodialysis patients are at increased risk of hepatitis B virus (HBV) infection and are poorly responsive to HBV vaccines. Current vaccine recommendations for hemodialysis patients utilize more than twice the amount of hepatitis B surface antigen (HBsAg) used for healthy adults and achieve lower immune responses. Methods: An open-label, single-arm, multicenter trial was conducted among adults 18 years of age and older who were initiating or undergoing hemodialysis who had not previously received hepatitis B vaccine. Participants received four doses of HepB-CpG (HEPLISAV-B®) (20 mcg rHBsAg + 3000 mcg CpG 1018, a Toll-like receptor 9 agonist) administered at 0, 4, 8, and 16 weeks. Participants are being followed for 68 weeks. This paper reports the final immunogenicity analysis of the primary endpoint at study week 20 and an interim safety analysis. Results: We enrolled 119 participants receiving hemodialysis who were followed for a median of 47.4 weeks. Of the 119 participants, 75 were in the per-protocol population. At week 20, the seroprotection rate (% with antibodies to hepatitis B surface antigen [anti-HBs] ≥ 10 mIU/mL) was 89.3% and the percentage of participants with anti-HBs ≥ 100 mIU/mL was 81.3%. The anti-HBs geometric mean concentration was 1061.8 mIU/mL. HepB-CpG was well tolerated with no observed safety concerns. Conclusion: In patients receiving hemodialysis, HepB-CpG given as four doses was well tolerated and induced very high anti-HBs concentrations and seroprotection in a very high proportion of recipients.